Pengaruh Kedisiplinan Tata Tertib Pada Regulasi Diri Santri - Nanda Mustika Meilan; Herlina (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2025)
This study aims to examine the effect of disciplinary regulations on students’ self-regulation in Islamic boarding schools (pesantren). Self-regulation is an essential ability that enables students to manage their thoughts, emotions, and behaviors in achieving learning goals, particularly within structured educational environments such as pesantren. This study employed a quantitative correlational design using simple linear regression analysis. The participants consisted of 252 male and female students from several pesantren in Gunung Pati District, Semarang, selected through proportional sampling. Data were collected using validated and reliable scales of disciplinary regulations and self-regulation.The results of the simple linear regression analysis indicated that disciplinary regulations did not have a significant effect on students’ self-regulation (β = 0.203; t = 1.60; p > 0.05). The coefficient of determination (R² = 0.022) showed that disciplinary regulations accounted for only 2.2% of the variance in students’ self-regulation, indicating a small effect size. These findings suggest that students’ self-regulation is not solely shaped by external discipline, but is more strongly influenced by internal factors such as intrinsic motivation, personal awareness, religious values, and social support. The study highlights the importance of integrating personal and spiritual development approaches alongside formal disciplinary systems in fostering students’ self-regulation within pesantren settings.